THE ROLE OF SALES ADMIN IN SUPPORTING ADMINISTRATIVE EFFICIENCY FOR SALES MARKETING DEPARTMENT PERFORMANCE AT NOVOTEL SEMARANG - Prabowo, Adinda Consita Yulianne; Satato, Yuniarto R (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examines the role of Sales Admin in supporting administrative efficiency for Sales Marketing Department performance at Novotel Semarang. Using a qualitative approach through interviews, observation, and document analysis, the research identified four key dimensions of administrative efficiency: process standardization, information accessibility, response timeliness, and resource allocation. These dimensions influence departmental performance through three pathways: enhanced sales productivity, improved client experience, and strengthened interdepartmental coordination. Findings show response times decreased from 24 hours to under 4 hours while administrative errors reduced by 40%. The research reveals Sales Admin functions as a strategic position rather than merely supportive. Being limited to a single hotel property, future research should explore comparative studies across multiple hotel brands to establish broader industry benchmarks for Sales Admin contributions. Keywords: Sales Admin; Administrative Efficiency; Hotel Marketing;Department Performance; Hospitality Management